VLP-Based Vaccines as a Suitable Technology to Target Trypanosomatid Diseases - Aline Maria Vasconcelos Queiroz; Johny Wysllas de Freitas Oliveira; Cláudia Jassica Moreno; Diego M. A. Guérin; Marcelo Sousa Silva (Vaccines, 2021)
Research on vaccines against trypanosomatids, a family of protozoa that cause neglected tropical diseases, such as Chagas disease, leishmaniasis, and sleeping sickness, is a current need. Today, according to modern vaccinology, virus-like particle (VLP) technology is involved in many vaccines, including those undergoing studies related to COVID-19. The potential use of VLPs as vaccine adjuvants opens an opportunity for the use of protozoan antigens for the development of vaccines against diseases caused by Trypanosoma cruzi, Leishmania spp., and Trypanosoma brucei. In this context, it is important to consider the evasion mechanisms of these protozoa in the host and the antigens involved in the mechanisms of the parasite–host interaction. Thus, the immunostimulatory properties of VLPs can be part of an important strategy for the development and evaluation of new vaccines. This work aims to highlight the potential of VLPs as vaccine adjuvants for the development of immunity in complex diseases, specifically in the context of tropical diseases caused by trypanosomatids.